UTILIZATION OF SOCIAL MEDIA IN THE DIGITAL AGE AS ACADEMIC RESOURCES AMONG BIOLOGY EDUCATION STUDENTS IN ABIA STATE, NIGERIA (UNIZIK Journal of STM Education, 2025)
The study investigated the utilization of social media (SM) as academic resources among Biology education students in Abia State Universities, adopting a descriptive survey research design. 123 students randomly drawn from, the 1500 biology education students in, the two universities served as the sample. A self-developed Questionnaire, face validated by experts with reliability coefficient of 0.76 established using Cronbach Alpha, was used for data collection. Data collected were analyzed using descriptive statistics and t-test for significant difference. Results revealed that MOUAU students indicated that Tiktok, Whatsapp and facebook are highly useful SM platforms, Snapchat, Instagram and Youtube are moderately useful, while the other stated SM platforms are just useful. ABSU students, on the other hand, indicated that Whatsapp and Facebook are highly useful, Tiktok and Youtube are moderately useful while Flickr, Tumblr, Spotify, Yelp, TripAdvisor, Angel list and Crunchbase are not useful. For frequency of usage; MOUAU students use Tiktok, Whatsapp and Facebook daily, Snapchat, Instagram, Twitter, Telegram and Youtube several times in a week while other SM platforms are used occasionally. ABSU students indicated that Tiktok and Whatsapp are used daily, Snapchat and facebook, several times a week, Flickr is never used and other platforms are used occasionally. Respondents, from both schools, indicated that Whatsapp and Facebook are utilized (Very High Extent), Tiktok, Snap chat and Youtube (High Extent) and Other SM platforms (Low extent). Also, a non-significant statistical difference was found in the extent of utilization of SM platforms as academic resources between students in the two universities. Recommendations were made among which is the need for educators to incorporate SM platforms usage into their instructional methods to enhance student engagement and academic achievement.
Keywords: Academic Resources, Biology Education Students, Digital Age, Social Media